EVALUATION OF ANALGESIC (IN VIVO) ACTIVITY OF ARIFLEX TABLET IN COMPARISON WITH DICLOFENAC AND ACECLOFENAC USING ACETIC ACID INDUCED WRITHING MODEL IN MICE - NIPANIKAR, SANJAY; SS, CHITLANGE (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The present study was conducted to evaluate analgesic activity of Ariflex Tablet which is a polyherbal formulation conceptualized and developed by Ari Healthcare Private in comparison to Aceclofenac and Diclofenac Tablet. Methods: Albino mice of either sex weighing 20–25 g were taken and divided into four groups with six animals in each group. Group 1 (Controlled Group) animals were starved overnight. Group 2 animals were orally administered with Diclofenac Tablet as Standard drug. Group 3 animals were orally administered with Aceclofenac Tablet as Standard drug and Group 4 Animals were orally administered with Ariflex Tablet. The test and standard drugs were orally administered with feeding needle after 1 h of injecting 1% acetic acid intraperitoneally in volume of 0.1 ml/10 g body weight. Writhing episodes were recorded for 30 min by counting the stretching. Results: All the tested formulations possess analgesic activity in acetic acid induced writhing model. Aceclofenac possesses strong analgesic activity compared to other formulations tested. In Ariflex Tablet Group, the number of writhes was 120.6±41.4. If compared to control group, the number of writhes was significantly less suggesting analgesic activity of Ariflex Tablet. Analgesic activity of Ariflex Tablet was close to that of Diclofenac Sodium. Conclusion: It can be concluded that Ariflex Tablet possesses significant analgesic activity. Ariflex Tablet can be used in the management of Osteoarthritis, Rheumatoid arthritis, Gouty arthritis, Lumbago, Sciatica, and Spondylitis.